Novel celecoxib analogues inhibit glial production of prostaglandin E2, nitric oxide, and oxygen radicals reverting the neuroinflammatory responses induced by misfolded prion protein fragment 90-231 or lipopolysaccharide. (November 2016) - Villa, Valentina; Thellung, Stefano; Bajetto, Adriana; Gatta, Elena; Robello, Mauro; Novelli, Federica; Tasso, Bruno; Tonelli, Michele; Florio, Tullio
Graphical abstract: Abstract: We tested the efficacy of novel cyclooxygenase 2 (COX-2) inhibitors in counteracting glia-driven neuroinflammation induced by the amyloidogenic prion protein fragment PrP90-231 or lipopolysaccharide (LPS). In search for molecules with higher efficacy than celecoxib, we focused our study on its 2, 3-diaryl-1, 3-thiazolidin-4-one analogues. As experimental models, we used the immortalized microglial cell line N9, rat purified microglial primary cultures, and mixed cultures of astrocytes and microglia. Microglia activation in response to PrP90-231 or LPS was characterized by growth arrest, morphology changes and the production of reactive oxygen species (ROS). Moreover, PrP90-231 treatment caused the overexpression of the inducible nitric oxide synthase (iNOS) and COX-2, with the consequent nitric oxide (NO), and prostaglandin E2 (PGE2 ) accumulation. These effects were challenged by different celecoxib analogues, among which Q22 (3-[4-(sulfamoyl)phenyl]-2-(4-tolyl)thiazolidin-4-one) inhibited microglia activation more efficiently than celecoxib, lowering both iNOS and COX-2 activity and reducing ROS release. During neurodegenerative diseases, neuroinflammation induced by amyloidogenic peptides causes the activation of both astrocytes and microglia with these cell populations mutually regulating each other. Thus the effects of PrP90-231 and LPS were also studied on mixed glial cultures containing astrocytes and microglia. PrP90-231 treatment elicited different responses in the co-cultures induced astrocyte proliferation and microglia growth arrest, resulting in a differential ability to release proinflammatory molecules with the production of NO and ROS mainly attributable on microglia, while COX-2 expression was induced also in astrocytes. Q22 effects on both NO and PGE2 secretion were more significant in the mixed glial cultures than in purified microglia, demonstrating Q22 ability to revert the functional interaction between astrocytes and microglia. These results demonstrate that Q22 is a powerful drug able to revert glial neuroinflammatory responses and might represent a lead to explore the chemical space around celecoxib frameworks to design even more effective agents, paving the way to novel approaches to contrast the neuroinflammation-dependent toxicity.